Hematogenous Renal Cell Carcinoma Metastasis in the Postoperative Temporal Bone - Konishi, Masaya (Case Rep Oncol, 2017)
Metastatic renal cell carcinoma (RCC) involving the temporal bone is a rare entity. It is usually asymptomatic and misdiagnosis as acute otitis media, mastoiditis, and Ramsay-Hunt syndrome in early onset is not uncommon. We report a case of RCC metastasis to the postoperative temporal bone in the middle of molecular targeted therapy. A 60-year-old man presented left facial palsy with severe retro-auricular pain and he also underwent left middle ear surgery for cholesteatoma more than 30 years before and had been aware of discontinuous otorrhea; therefore, initially we speculated that facial palsy was derived from recurrent cholesteatoma or Ramsay-Hunt syndrome. Exploratory tympanotomy revealed RCC metastasis and postoperative MR indicated hematogenous metastasis. To the best of our knowledge, no report was obtained on temporal bone metastasis in the middle of chemotherapy or hematogenous metastasis in the postoperative middle ear. Metastasis in the temporal bone is still a possible pathological condition despite the development of present cancer therapy. Besides, this case indicates that hematogenous metastasis can occur in the postoperative state of the temporal bone.